Tetraphenylethylene-doped covalent organic frameworks as a highly efficient aggregation-induced electrochemiluminescence emitter for ultrasensitive miRNA-21 analysis - Shu, Wen-Yi; Su, Ruiqi; Yao, Linli; Xiao, Yao; Chen, Miao-Miao; Wen, Wei; Wang, Shengfu; Xiong, Chengyi; Zhang, Xiuhua (Advanced Sensor and Energy Materials, 2023)
MicroRNAs (miRNAs) as a well-known kind of cancer marker are closely associated with the formation and metastasis of tumors. Here, a novel tetraphenylethylene (TPE)-doped covalent organic frameworks (TPE-COFs) with strong aggregation-induced electrochemiluminescence (AIECL) response was synthesized and introduced to construct an ultrasensitive biosensor for the detection of miRNA-21. The strong aggregation-induced emission (AIE) response was obtained because the molecular motion of TPE was restricted by COFs which had the porosity and highly ordered topological structure. Meanwhile, the porous structure of COFs allowed TPE to react with electrochemiluminescence (ECL) coreactants more effectively. Furthermore, COFs significantly improved the electron transport efficiency of the entire ECL system. All of these endowed the TPE-COFs with superior AIECL performance. Then, a TPE-COFs based ECL resonance energy transfer (ECL-RET) system was constructed for ultrasensitive miRNA-21 biosensing with differential signal readout. The proposed assays exhibited excellent sensitivity with a wide dynamic range from 10 aM to 1 pM and a low detection limit of 2.18 aM. Therefore, these indicated that doping TPE in COFs was a creative way to develop functional COFs and provided an effective way for enhancing AIECL. Furthermore, this work boarded the application of AIECL in analytical chemistry.